Role of neuropsin in parvalbumin immunoreactivity changes in hippocampal basket terminals of mice reared in various environments - Suzuki, Harumitsu; Kanagawa, Dai; Nakazawa, Hitomi; Tawara-Hirata, Yoshie; Kogure, Yoko; Shimizu-Okabe, Chigusa; Takayama, Chitoshi; Ishikawa, Yasuyuki; Shiosaka, Sadao (Frontiers in Cellular Neuroscience, 2014)
In vitro approaches have suggested that neuropsin (or kallikrein 8/KLK8), which controls gamma-aminobutyric acid (GABA) neurotransmission through neuregulin-1 and its receptor (ErbB4), is involved in neural plasticity (Tamura et al., 2012, 2013). In the present study, we examined whether parvalbumin (PV)-positive neuronal networks, the majority of which are ErbB4-positive GABAergic interneurons, are controlled by neuropsin in tranquil and stimulated voluntarily behaving mice. PV-immunoreactive fibers surrounding hippocampal pyramidal and granular neurons in mice reared in their home cage were decreased in neuropsin-deficient mice, suggesting that neuropsin controls PV immunoreactivity. One- or two-week exposures of wild mice to novel environments, in which they could behave freely and run voluntarily in a wheel resulted in a marked upregulation of both neuropsin mRNA and protein in the hippocampus. To elucidate the functional relevance of the increase in neuropsin during exposure to a rich environment, the intensities of PV-immunoreactive fibers were compared between neuropsin-deficient and wild-type mice under environmental stimuli. When mice were transferred into novel cages (large cages with toys), the intensity of PV-immunoreactive fibers increased in wild-type mice and neuropsin-deficient mice. Therefore, behavioral stimuli control a neuropsin-independent form of PV immunoreactivity. However, the neuropsin-dependent part of the change in PV-immunoreactive fibers may occur in the stimulated hippocampus because increased levels of neuropsin continued during these enriched conditions.